Enantioselective Au(I)/Au(III) redox catalysis enabled by chiral (P,N)-ligands - Chintawar, Chetan C.; Bhoyare, Vivek W.; Mane, Manoj V.; Patil, Nitin T. (Journal of the American Chemical Society, 2022)
Presented herein is the first report of enantioselective Au(I)/Au(III) redox catalysis, enabled by a newly designed hemilabile chiral (P,N)-ligand (ChetPhos). The potential of this concept has been demonstrated by the development of enantioselective 1,2-oxyarylation and 1,2-aminoarylation of alkenes which provided direct access to the medicinally relevant 3-oxy- and 3-aminochromans (up to 88% yield and 99% ee). DFT studies were carried out to unravel the enantiodetermining step, which revealed that the stronger trans influence of phosphorus allows selective positioning of the substrate in the C-2-symmetric chiral environment present around nitrogen, imparting a high level of enantioselectivity.